2019
DOI: 10.1111/ijcp.13316
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cutaneous adverse reactions associated with allopurinol or febuxostat in real‐world patients: A nationwide study

Abstract: Summary Aims Allopurinol carries a well‐known risk of cutaneous adverse reactions (CARs). Although febuxostat, a xanthine‐oxidase inhibitor with different chemical structure, has been considered an alternative to allopurinol, post‐marketing case reports of life‐threatening febuxostat‐related CARs have been reported. We aimed to compare the risk of CARs between allopurinol and febuxostat in real‐world settings and to assess the impact of the market entry of febuxostat on allopurinol use and associated CARs. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
1
22
1
1
Order By: Relevance
“…In a Taiwanese population-based cohort, cutaneous adverse reaction incidence rates were higher in allopurinol versus febuxostat, 15.37 vs 3.48 per 1000 person-years 9. Although our HSR rates in allopurinol exposed were similar to those in the Taiwanese study at 24/1000 person-years, rates in febuxostat-exposed patients were much higher at 31/1000 person-years in our study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In a Taiwanese population-based cohort, cutaneous adverse reaction incidence rates were higher in allopurinol versus febuxostat, 15.37 vs 3.48 per 1000 person-years 9. Although our HSR rates in allopurinol exposed were similar to those in the Taiwanese study at 24/1000 person-years, rates in febuxostat-exposed patients were much higher at 31/1000 person-years in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Similar studies have not been conducted in populations from the USA or the European countries. Comparative studies of allopurinol versus febuxostat are limited to some ethnicities only 9…”
Section: Introductionmentioning
confidence: 99%
“…MCARs feature sparse maco-papular rash and no other organ involvement and quick resolution after drug discontinuation. In contrast, severe CARs (SCARs), characterized by widespread skin lesions, fever, organ involvement, and a mortality rate of 10 to 32% [3,10,11], are rare, although their frequency seems increased in Asians and some other non-Caucasian ethnicities [3,9,12,13]. Allopurinol-induced SCARs include Stevens-Johnson syndrome/toxic epidermal necrosis (SJS/TEN), drug reaction with eosinophilia and systemic symptoms (DRESS), and acute generalized exanthematous pustulosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the incidence of SCARs due to allopurinol was higher in Asian than Caucasian populations. The incidence was estimated at 0.16% per year in Thailand [16], and for patients with chronic renal insufficiency (CRI), 2% and 2.3% per year in Korea [17] and Taiwan [9], respectively. More recently, the incidence of SCARs between 2008 and 2015 in Taiwan has been estimated at 0.10% per year; older estimations based on 2001-2004 data were close to 0.30% per year [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation